GENDING DONGKANG MENEK BIU SEBAGAI MATERI PEMBELAJARAN DASAR GENDER WAYANG DI SANGGAR DEWA RUCI, DESA SIBANG KAJA - I Ketut Gede Rudita -; I Wayan Arissusila -; Ida Bagus Karang Dyatmika - (UNHI PRESS, 2023)
ABSTRACT Education has an important role in introducing individuals to culture and shaping their behavior according to the culture adopted. Education can be divided into 3, namely formal, non-formal and informal. Gending dongkang menek biu is a form of non-formal education to preserve the art of gender wayang in Sibang Kaja Village. Based on this, the problems that can be raised are: What are the forms, methods and implications of learning gending dongkang menek biu as basic learning material for gender wayang at the Dewa Ruci Studio, Sibang Kaja Village. This research uses observation, interview and document stadi methods. The collected data was analyzed using qualitative descriptive techniques. This research uses aesthetic theory, constructivism and behaviorism. The result is the form of gending dongkang menek biu as basic learning material for wayang gender in Sibang Kaja Village, namely the structure consists of three parts which can be said to be palette 1, palette 2, and palette 3. The learning method for gending dongkang menek biu as basic learning material for wayang gender in Sibang Kaja Village uses the pelvic meguru, munyi meguru, and ear meguru methods. The implications of learning the gending dongkang menek biu as basic learning material for wayang gender in Sibang Kaja Village are in the cognitive, adaptive and psychomotor domains. Keywords: Gending Dongkang Menek Biu, Basic Learning, Gender Puppet